Vector flow mapping analysis of left ventricular vortex performance in type 2 diabetic patients with early chronic kidney disease - Chen, Xiaoxue; Qiu, Fang; Wang, Wei; Qi, Zhengqin; Lyu, Damin; Xue, Kun; Sun, Lijuan; Song, Degang (BMC cardiovascular disorders, 2023)
Background Diabetes is the leading cause of chronic kidney disease (CKD) and contributes to an elevated incidence of diastolic dysfunction in the early stages of CKD. Intracardiac vortex is a novel hemodynamic index for perceiving cardiac status. Here, we visualized left ventricular (LV) vortex characteristics using vector flow mapping (VFM) in type 2 diabetic patients with early CKD. Methods This cross-sectional study included 67 controls and 89 type 2 diabetic patients with stages 2-3a CKD. All subjects underwent transthoracic echocardiographic examination. LV anterior vortex during early diastole (E-vortex), atrial contraction (A-vortex) and systole (S-vortex) were assessed using VFM in the apical long-axis view. Its relation to glycemia or LV filling echocardiographic parameters were further analyzed using correlation analysis. Results Type 2 diabetic patients with early CKD had a small area (439.94 ± 132.37 mm 2 vs. 381.66 ± 136.85 mm 2 , P = 0.008) and weak circulation (0.0226 ± 0.0079 m 2 /s vs. 0.0195 ± 0.0070 m 2 /s, P = 0.013) of E-vortex, but a large area (281.52 ± 137.27 mm 2 vs. 514.83 ± 160.33 mm 2 , P ˂ 0.001) and intense circulation (0.0149 ± 0.0069 m 2 /s vs. 0.0250 ± 0.0067 m 2 /s, P < 0.001) of A-vortex compared to controls. CKD patients with poorly controlled hyperglycemia had stronger A-vortex (area: 479.06 ± 146.78 mm 2 vs. 559.96 ± 159.27 mm 2 , P = 0.015; circulation: 0.0221 ± 0.0058 m 2 /s vs. 0.0275 ± 0.0064 m 2 /s, P < 0.001) and S-vortex (area: 524.21 ± 165.52 mm 2 vs. 607.87 ± 185.33 mm 2 , P = 0.029; circulation: 0.0174 ± 0.0072 m 2 /s vs. 0.0213 ± 0.0074 m 2 /s, P = 0.015), and a longer relative duration of S-vortex (0.7436 ± 0.0772 vs. 0.7845 ± 0.0752, P = 0.013) than those who had well-controlled hyperglycemia. Glycemia, and E/A (a LV filling parameter) were respectively found to had close correlation to the features of A-vortex and S-vortex (all P < 0.05). Conclusions Abnormal LV vortices were detected in type 2 diabetic patients with early CKD using VFM, especially in those who neglected hyperglycemic control. LV vortex might be a promising parameter to slow or halt the hyperglycemia-induced diastolic dysfunction in early CKD.